Social adjustments reviewed from the social intelligence of final-year students - Mujib Mujib; Farida As'ari; Mery lestari; Uray Endang Kusumajaya; Tri Pratomo; Sulaiman Sulaiman (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2022)
This study aims to determine the effect of social intelligence on the social adjustment of final-year students of the D4 Mechanical Engineering Program at the Pontianak State Polytechnic. The hypothesis in this study is that there is a significant effect between social intelligence and social adjustment of final-year students. Respondents in this study were 49 final-year students of the D4 Mechanical Engineering Study Program at the Pontianak State Polytechnic. The data collection tool uses a social adjustment scale and a social intelligence scale—data analysis using a simple linear regression technique with the help of SPSS 22.00 for the Windows program. The results of this study indicate that there is a very significant positive effect between social adjustment and social intelligence, which has a correlation coefficient (r) = 0.851 and p = 0.00 (p < 0.001). The higher the level of social intelligence, the higher the social adjustment of final-year students. On the other hand, the lower the level of social intelligence, the lower the social adjustment. Social intelligence affects social adjustment by (r2) = 72.5%.